1999
DOI: 10.3168/jds.s0022-0302(99)75274-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct-Fed Fibrolytic Enzymes on the Lactational Performance of Dairy Cows

Abstract: In trial 1, 30 midlactation (213 d in milk) Holstein cows were randomly assigned to a control or enzyme treatment in a two-period crossover design and were fed a total mixed ration based on alfalfa hay and silage. Cows on the enzyme treatment received an enzyme solution containing cellulases and xylanases, which was sprayed on the forage component of the ration at a rate of 1.65 ml/kg of forage dry matter (DM) between 8 and 24 h prior to feeding. Cows consuming the forage treated with enzyme produced more milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
85
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 13 publications
17
85
1
13
Order By: Relevance
“…On the other hand, several researchers recorded an increase in DMI of dairy cows when fibrolytic enzymes was applied to forage before mixing with other ingredients (Lewis et al, 1999) or applied to TMR or concentrate portion of the diet (Bowman et al, 2002;Ware & Zinn, 2005). However, the effects of fibrolytic enzymes on DMI appear to be vary among enzymes products and the method of applying of enzymes (Bowman et al, 2002) A number of studies have examined the effects of fibrolytic exogenous enzymes on digestibility and milk production in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several researchers recorded an increase in DMI of dairy cows when fibrolytic enzymes was applied to forage before mixing with other ingredients (Lewis et al, 1999) or applied to TMR or concentrate portion of the diet (Bowman et al, 2002;Ware & Zinn, 2005). However, the effects of fibrolytic enzymes on DMI appear to be vary among enzymes products and the method of applying of enzymes (Bowman et al, 2002) A number of studies have examined the effects of fibrolytic exogenous enzymes on digestibility and milk production in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of fibrolytic enzymes on DMI appear to be vary among enzymes products and the method of applying of enzymes (Bowman et al, 2002) A number of studies have examined the effects of fibrolytic exogenous enzymes on digestibility and milk production in dairy cows. In some studies, dietary addition of fibrolytic enzymes either to forages or concentrate portion increased milk production from 5-16% (Lewis et al, 1999;Gado et al, 2009;Holtshausen et al, 2011) as noticed at the current study but no milk response was reported in others (Elwakeel et al, 2007;Bernard et al, 2010). Furthermore, these enhancement in milk yield at the current study are in line with those found by Guerra et al (2007) who used Fibrozyme in diet containing alfalfa hay and they reported that Fibrozyme supplementation increased milk yield, which may be due to improved utilization of nutrients in digestive tract and in rumen and increased gain of net energy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the increase in bacterial numbers disappeared when higher levels of enzyme supplementation were used. This quadratic response may explain the non-linear dose responses typically observed in vivo Lewis et al 1999;Kung et al 2000).…”
Section: Stimulation Of Rumen Microbial Populationsmentioning
confidence: 92%
“…McAllister et al (1999), avaliando o desempenho de novilhos em confinamento, observaram aumentos de 5,99 kg/dia para 6,72 kg/dia na ingestão de MS e de 0,94 kg/dia para 1,16 kg/dia no ganho médio diário com a suplementação enzimática (celulase e xilanase). Lewis et al (1995), em estudo com vacas em lactação consumindo forragem, também verificaram aumentos de 5 a 25% no consumo e na produção de leite com a adição de enzimas fibrolíticas exógenas na dieta.…”
Section: Introductionunclassified